Involvement of Lipids and Lipid Mediators in Inflammation and Atherogenesis - Kotlyarov, Stanislav (Current Medicinal Chemistry, 2025)
Atherosclerosis is the pathophysiological basis for major diseases, such as coronary heart disease, cerebral stroke, and peripheral arterial disease, which have become epidemic in modern Western society. Atherosclerosis has a complex nature that involves mutually related immune and metabolic mechanisms. Many cells of the vascular wall and peripheral bloodstream, including endothelial cells, monocytes and macrophages, platelets, and others, are involved in the development and progression of atherosclerosis. These cells perform a number of innate immune functions, disorders of which are associated with atherosclerosis. Furthermore, lipids are not only a morphological substrate but also important participants in the development of atherosclerosis. They are involved in the development and resolution of inflammation and mediate vascular cell function.
Keywords: inflammation